PENILAIAN HASIL CYSTATIN C PADA PASIEN GANGGUAN FUNGSI GINJAL DI LABORATORIUM PRODIA CIBUBUR - Aminah Aminah; Putu Ayu Parwati; Moh. Adreng Pamungkas; Diah Prihatiningsih (Multidisciplinary Indonesian Center Journal (MICJO), 2024)
Kidney function disorders refer to a condition where the kidneys' ability to filter metabolic waste from the blood and excrete it through urine is compromised. Cystatin C serves as a sensitive and specific biomarker for measuring glomerular filtration rate, accurately reflecting kidney function. This study aims to evaluate Cystatin C levels based on gender among patients with kidney function disorders at the Prodia Cibubur clinic laboratory. The research was conducted from February to March 2023 using a descriptive cross-sectional approach. The sample comprised 120 patients with kidney function disorders selected through total sampling. The findings indicate that 16 patients (13.3%) had normal Cystatin C levels, while 104 patients (86.7%) had elevated Cystatin C levels. Notably, among males, 61 individuals (50.8%) tended to exhibit higher Cystatin C levels, suggesting a greater potential for kidney function disorders due to factors such as activity intensity, body mass influence, and hormonal factors.